A study on the factors effecting yield spread of 10 years Malaysian Government Securities / Mohd Amin Abdullah - Abdullah, Mohd Amin (Faculty of Business and Management, 2011)
This study tries to investigate the factor that will contribute to the changes of yield spread Malaysian Bond Market. The quarterly 10 years Malaysian Government Securities (MGS10) bond yield, Gross Domestic Product (GDP), Interest rate and Consumer Price Index (CPI), running from first quarter 2007 until fourth quarter 2010 are collected and Multiple Linear Regression Model are used in this investigation. The results from models reveal that there is significant relationship between macroeconomic factors and 10 years Malaysian government securities bond yield. MGS10 bond yield are positively affected with GDP and CPI and react negatively with the Interest rate. The findings in this investigation are useful for market participants, investors, professional portfolio managers, government agencies and financial literature who are concerned with the bond yield in Malaysia Bond market.